On the taxonomic validity of Indian ground spiders: I. Genus Scopoides Platnick, 1989 (Araneae: Gnaphosidae) - Sankaran, Pradeep M.; Caleb, John T.d.; Caleb, John T.d.; Sebastian, Pothalil A. (Zootaxa, 2019)
Indian Scopoides species have been revised. Three new combinations are proposed: Poecilochroa kuljitae (Tikader, 1982) comb. nov., Megamyrmaekion pritiae (Tikader, 1982) comb. nov. and Megamyrmaekion tikaderi (Gajbe, 1987) comb. nov.. Scopoides maitraiae (Tikader & Gajbe, 1977) and Scopoides samarae Gawande & Bodkhe, 2018 are synonymized with Drassodes luridus (O. Pickard-Cambridge, 1874). All the examined type materials are imaged and supplementary descriptions for P. kuljitae comb. nov., M. pritiae comb. nov. and M. tikaderi comb. nov. are provided.